Biochemical genetics of methylglyoxal dehydrogenases in the laboratory rat (Rattus norvegicus) - Bender K; Seibert, R. T; Wienker, T. F; Křen, Vladimír; Pravenec, Michal; Bissbort, S (Biochemical genetics, 1994)
A genetic locus controlling the electrophoretic mobility of a methylglyoxal dehydrogenase (EC 1.2.1.23) in the rat is described. The locus, designated Mgd1, is expressed in liver and kidney. Inbred rat strains have fixed either allele Mgd1a or allele Mgd1b. Codominant expression is observed in heterozygotes, providing evidence for a tetrameric enzyme structure. Backcross progenies showed the expected 1:1 segregation ratio, and there is evidence that Mgd1 is linked to Pep3 and Fh1 on chromosome 13. There is also evidence for two additional methylglyoxal dehydrogenases: Mgd2, present in liver and kidney, and Mgd3, present only in heart.
Keywords: ledviny; Crosses, Genetic; alely; myokard; dominantní geny; zvířata; Rats; Genes, Dominant; Protein Conformation; Aldehyde Oxidoreductases; ektroforéza na škrobovém gelu; Genes; Polymorphism, Genetic; aldehydoxidoreduktasy; křížení genetické; mužské pohlaví; konformace proteinů; polymorfismus genetický; Muscle Proteins; Organ Specificity; Electrophoresis, Starch Gel; svalové proteiny; krysa rodu Rattus; ženské pohlaví; Female; Rats, Inbred Strains; Liver; izoenzymy; orgánová specificita; Animals; Kidney; Isoenzymes; játra; Myocardium; Male; geny; Alleles